Studia nad Kształtem Błonowych Powłok Obrotowych w Stanie Plastycznym - Marciniak, Z. (Engineering Transactions, 1958)
Devoted to a discussion of the forms of thin walled shells of revolution treated as plastic membranes. The load is composed of an axially symmetric normal pressure p and edge forces. The simultaneous satisfaction of the equilibrium conditions and the yield condition in the form […], where S, and So are forces per unit length of cross-section in the meridional and the parallel direction, leads to a relation between the inclination angle of the tangent to the shell at the given point and distance of that point from the axis of the shell. This relation enables the graphical determination of the form of the shell corresponding to the given boundary conditions. Examples of shell forms obtained for various loads are given, and technological processes indicated for which the sheet worked takes a form approaching that determined theoretically.